A structural equation modelling to explore the determinants of mental health disorders among reproductive-aged women in Nepal: a nation-wide cross-sectional survey - Md. Ashfikur Rahman; Mortuja Mahamud Tohan; Sayeeda Zaman; Md. Amirul Islam; Md. Sazedur Rahman; Md. Hasan Howlader; Satyajit Kundu (BMC Psychiatry)
Abstract Background Similar to other countries, reproductive-age women in Nepal frequently encounter diverse mental disorders, yet they receive inadequate screening and attention. This research seeks to address this gap by conducting a comprehensive examination of the prevalence and factors associated with mental disorders of reproductive-age women in Nepal. Methods This study used the nationally representative Nepal Demographic and Health Survey 2022 dataset to examine the association between mental disorders and potential confounders. Screening tools for Generalized Anxiety Disorder (GAD-7) and Patient Health Questionnaire (PHQ-9) were employed, and descriptive and inferential statistics, including linear regression and structural equation modeling, were utilized in the analysis. Results The study found that 22% of Nepalese women aged 15 to 49 reported anxiety symptoms, while 5% reported depressive symptoms. The Structural Equation Modeling (SEM) reveals that anxiety had the most significant positive effect on depression (β = 0.683, p < 0.001), followed by emotional violence (β = 0.139, p < 0.001). Marital status (β = 0.072, p < 0.001) and the presence of genital discharge (β = 0.084, p < 0.001) or ulcer (β = 0.058, p < 0.001) in the last 12 months were also associated with higher levels of depression. Conversely, self-rated health status (β=-0.121, p < 0.001) was negatively associated with depression, indicating that better-perceived health was linked to lower levels of depression. Conclusion Although the prevalence of anxiety symptoms is higher than that of depression, there is a positive relationship between these two. Consequently, it is crucial to address the identified factors contributing to anxiety and depression in this population group through behavioral and policy interventions to enhance the mental well-being of reproductive-age women.